Investigation on the Effect of Opening Size and Position on Wind-Driven Cross-Ventilation in an Isolated Gable Roof Building - Hacımurat Demir; Burak Aktepe (Applied Sciences)
In this study, the influence of window opening sizes and positions on wind-induced cross ventilation performance in an isolated gable roof building was numerically investigated using the k-ω SST turbulence model. The results obtained from numerical analyses to evaluate the ventilation efficiency of different configurations show that larger inlet openings significantly increase the ventilation rates and the WO5 model reaches the highest ventilation rate of 0.004089 m3/s with an improvement of 37.27% compared to the reference model. As with the WO1 model, smaller inlet openings limited the air intake, reducing ventilation efficiency and indoor air quality. In terms of outlet window opening sizes, the LO5 model showed the highest ventilation efficiency, improving ventilation by 28% compared to reference model, while smaller outlet openings, as in the LO1 model, were associated with significantly lower performance. Additionally, when evaluating window opening locations, configurations with higher exit openings generally exhibited superior ventilation rates. The best overall ventilation performance was achieved in the Upper-Lower configuration at 0.003129 m3/s. The findings emphasized the critical role of window design in natural ventilation performance. Larger and strategically located window openings optimize airflow, increase ventilation efficiency and improve indoor air quality, providing valuable information for energy-efficient building design.